The Role of Reflection in Addressing the Social Responsibility Mandate of Teacher Education - Falkenberg, Thomas (Phronesis, 2013)
This article makes the case that a teacher’s personal qualities should be considered to be of great importance to being a teacher and that pre- and inservice teacher education has a social responsibility mandate. Developing personal qualities in teacher education is an important way in which teacher education can address its social responsibility mandate and, conversely, this mandate can provide the perspective from which the value of teacher’s personal qualities for teaching can be judged. Finally, the article discusses the role of reflective thinking and reflective practice in addressing the social responsibility mandate of teacher education and identifies characteristics of reflective practices that seem particularly suitable for developing a teacher’s personal qualities relevant for addressing the social responsibility mandate of teacher education.